Antibody Combinations Targeting the Essential Antigens CyRPA, RH5, and MSP-119 Potently Neutralize Plasmodium falciparum Clinical Isolates From India and Africa. (29th September 2020) - Singh, Hina; Mian, Syed Yusuf; Pandey, Alok K; Krishna, Sri; Anand, Gaurav; Reddy, K Sony; Chaturvedi, Neha; Bahl, Vanndita; Hans, Nidhi; Shukla, Man Mohan; Bassat, Quique; Mayor, Alfredo; et al.
Abstract: Background: Targeting multiple key antigens that mediate distinct Plasmodium falciparum erythrocyte invasion pathways is an attractive approach for the development of blood-stage malaria vaccines. However, the challenge is to identify antigen cocktails that elicit potent strain-transcending parasite-neutralizing antibodies efficacious at low immunoglobulin G concentrations feasible to achieve through vaccination. Previous reports have screened inhibitory antibodies primarily against well adapted laboratory parasite clones. However, validation of the parasite-neutralizing efficacy against clinical isolates with minimal in vitro cultivation is equally significant to better ascertain their prospective in vivo potency. Methods: We evaluated the parasite-neutralizing activity of different antibodies individually and in combinations against laboratory adapted clones and clinical isolates. Clinical isolates were collected from Central India and Mozambique, Africa, and characterized for their invasion properties and genetic diversity of invasion ligands. Results: In our portfolio, we evaluated 25 triple antibody combinations and identified the MSP-Fu+CyRPA+RH5 antibody combination to elicit maximal parasite neutralization against P. falciparum clinical isolates with variable properties that underwent minimal in vitro cultivation. Conclusion s: The MSP-Fu+CyRPA+RH5 combination exhibited highly robust parasite neutralization against P. falciparum clones and clinical isolates, thus substantiating them as promising candidate antigens and establishing a proof of principle for the development of a combinatorial P. falciparum blood-stage malaria vaccine. Abstract : Our study has identified an antigen combination that elicits potent strain-transcending parasite-neutralizing antibodies that efficaciously inhibit worldwide P falciparum strains through distinct mechanisms and establishes a proof of concept for the development of a combinatorial blood-stage malaria vaccine.